Ecological System of Open Platform and Development of the Third Party Service Market - Xiaoling Chen (Dianxin kexue)
With the coming of mobile internet, the trend of traditional communication industry has become decentralized, clustering, ecological, and“open platform”has been irreversible. Emerging industrial power, such as terminal producers and internet companies, has gained the first mover advantage in the control of the mobile internet industry chain by using the open platform. In order to help telecom operators to insure and reconfigure the discourse power, the ecological system of open platform and the third party service market were studied, and the strategy and suggestion for telecom operators to build open platform were put forward.